2015
DOI: 10.5505/agri.2015.14238
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pain, depression symptoms and daily living independency level among geriatrics in nursing home

Abstract: SummaryObjectives: The aim of this study was to investigate pain, depression and independence in activities of daily living in geriatric residents of nursing homes, as well as to evaluate the relationship between these parameters. Methods: 186 nursing home residents, aged 65 to 90 years, were enrolled in the study. Their socio-demographic features, depression levels, pain levels and independence in activities of daily living were evaluated using a socio-demographic assessment form, the Geriatric Depression Sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 32 publications
(34 reference statements)
1
11
0
1
Order By: Relevance
“…This study focused on the characteristics and trends of chronic pain among middle aged and elderly people in China. It showed that 30.13% of the middle aged and elderly Chinese people suffered from chronic body pain, which was consistent with pain prevalence in previous studies, usually between 28.9% and 59.3% [13].…”
Section: Discussionsupporting
confidence: 90%
“…This study focused on the characteristics and trends of chronic pain among middle aged and elderly people in China. It showed that 30.13% of the middle aged and elderly Chinese people suffered from chronic body pain, which was consistent with pain prevalence in previous studies, usually between 28.9% and 59.3% [13].…”
Section: Discussionsupporting
confidence: 90%
“…Other health complaints reported by institutionalized elderly people from the north coast of Rio Grande do Sul were difficulty walking and vision problems, which are related to the independence and autonomy of functional capacity. The investigation of pain, the presence of depression and independence in activities of daily living are fundamental to determining the measures necessary to promote the health and well-being of the geriatric population 31 .…”
Section: Resultsmentioning
confidence: 99%
“…To this end, wearable monitoring technology and its integration into tele-health systems is necessary. Tele-consultation appears convenient for patients unable to be moved around, either because they are in a closed institution (a geriatric hospital, protect contest, a prison or psychiatric ward for example) or because they live in areas difficult to reach (namely rural areas) [13][14][15]. Moreover, growing evidence is demonstrating that, among the various advantages provided by tele-health systems in the elderly, behavioral improvement may have a pivotal role [6].…”
Section: Introductionmentioning
confidence: 96%